John Cassian and the Jews - Heisey, Daniel J. (Cistercian studies quarterly, 2006)
The article discusses the monastic conversion of life in the works of author John Cassian. The desert monks that Cassian portrayed left behind their family and friends. Monastic life is all about personal and communal conversion. This conversion causes concern for Christians and Jews. Both feared and resisted attempts to be converted to the other. Cassian puts this fear in the context of the virtue of "discretio" or its absence.